Integration and Assessment of Biophysical Resources of Sikar District for Sustainable Land Use Planning - Singh Singh, Nepal; Vangani, N S; Singh, Surendra (Annals of Arid Zone, 2016)
In Sikar district, 18 Major Land Resources Units (MLRUs), having homogeneity of biophysical resources such as landform, soil, vegetation, surface and ground water and present landuse, were identified, characterized and assessed for their potentialities and limitations. Information on each resource unit was further evaluated and assessed for sustainable landuse planning and development in the district. The land resources units, qualifying for land capability classes lIe and Ilk, having 3388 km2 (43.38%) area, low intensity of degradation and reasonably good quality of water, are most suitable for both rain-fed farming with agroforestry system and irrigated farming with agrohorticulture system. The marginal lands with capability class lYe, suffering from various land degradation hazards, having 2086 km2 (26.97%) area, and poor ground water potential, are suitable for agroforestry, pasture and silvi-pastoral systems. The remaining 2258 km2 (29.20%) area, not suitable for cultivation due to soil depth, wind and water erosion, high salinity and waterlogging, could be developed for silvopasture using salt-tolerant plant species and for salt extraction.